Hak Cerai Isteri - Amalia, Fatma (Musawa Jurnal Studi Gender dan Islam, 2004)
In principle, divorce is an unwanted decision for married couples. However, sometimes this is undeniable for many reasons. In Islam, divorce is perceived as an emergency exist for those who could not bare the marriage any longer. What is important to underline is the perceived opinion that it is only the husband who has the authority to divorce his wife. This article attempts at questioning this opinion. In addition, it debates different rights for husband and wife to get a divorce as stated in the fiqh text (known as talaq and kbulii').